Precise Point Positioning (PPP): Method and its Geodetic Usage - Timilsina, Sushmita (Journal on Geoinformatics, Nepal, 2019)
Combining the precise satellite positions and clocks correction with dual-frequency GNSS receiver, PPP is able to provide position solutions at centimeter- decimeter level. PPP can be regarded as a global positioning approach because its position solutions referred to a global reference frame. As a result, PPP provides much greater positioning consistency than the differential approach in which position solutions are relative to the local base station or stations. Due to this, today PPP has been the demand of large number of market.